2003
DOI: 10.2134/jeq2003.2379
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Chemical, Thermal, and Microbiological Approach to Compost Stability Evaluation

Abstract: The evaluation of compost stability is of the utmost importance for the reliability of composting as a recycling strategy. To date there is no single parameter that can give a sure indication of the stability of composts from different starting materials. This paper investigates different methods of evaluating the dynamics of transformation of materials and the stability level of the end products in a composting process. The following parameters were determined on compost samples of different ages from cotton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 38 publications
2
46
0
6
Order By: Relevance
“…These findings coincide with Castillo (2002) who obtained 29.72% of organic-C content when using cattle and bovine manures. Such a behavior has been published by several researchers (Mondini et al, 2003) stating that the increase of organic-C concentration can be a result of the C usage from the initial organic residues by microorganisms in order to build new cellular materials, which can be re-used in the vermicomposting process later on, although such an increase do not coincide with Nogales et al (2005) and Santamaría-Romero et al (2001) who observed a decrease in organic-C content due to losses in the form of CO 2 in the process.…”
Section: Resultsmentioning
confidence: 69%
“…These findings coincide with Castillo (2002) who obtained 29.72% of organic-C content when using cattle and bovine manures. Such a behavior has been published by several researchers (Mondini et al, 2003) stating that the increase of organic-C concentration can be a result of the C usage from the initial organic residues by microorganisms in order to build new cellular materials, which can be re-used in the vermicomposting process later on, although such an increase do not coincide with Nogales et al (2005) and Santamaría-Romero et al (2001) who observed a decrease in organic-C content due to losses in the form of CO 2 in the process.…”
Section: Resultsmentioning
confidence: 69%
“…The first transition, at approx. 124°C, is attributed to residual water removal (free and bound water) from the samples [1,26] . The three transitions in the range 180-600°C, approx.…”
Section: Thermal Analysismentioning
confidence: 99%
“…275, 381 and 475°C, are due to different organic pools. Mass loss at 731°C is due to the CaCO 3 decarboxylation [1,16] . The presence of CaCO 3 is typical of these samples because is a part of animal Table 4: TG in air flow (100 ml/min): main thermogravimetric weight loss (% of initial sample) and temperature ranges in which they occurred T range (°C) 1 : M mass variation as % of initial sample mass, *: Represent 5% significant level feed.…”
Section: Thermal Analysismentioning
confidence: 99%
See 2 more Smart Citations